Cellular and Molecular Adaptation of Arabian Camel to Heat Stress - Hoter, Abdullah; Rizk, Sandra; Naim, Hassan Y. (Frontiers in Genetics, 2019)
To cope with the extreme heat stress and drought of the desert, the Arabian camel (Camelus dromedarius) has developed exceptional physiological and biochemical particularities. Previous reports focused mainly on the physiological features of Arabian camel and neglected its cellular and molecular characteristics. Heat shock proteins are suggested to play a key role in the protein homeostasis and thermotolerance. Therefore, we aim by this review to elucidate the implication of camel HSPs in its physiological adaptation to heat stress and compare them with HSPs in related mammalian species. Correlation of these molecules to the adaptive mechanisms in camel is of special importance to expand our understanding of the overall camel physiology and homeostasis.